Pengaruh Lingkungan Kerja dan Kompensasi terhadap Kinerja Karyawan di PT GOS Indoraya - Anindya Najmina Nareswari; Bunga Karnelia; Keysha Azahra Ramadhani (Universitas 45 Surabaya, 2024)
This study aims to analyze the influence of work environment and compensation on employee performance at PT GOS Indoraya. Through a literature review and case analysis, this study concludes that both a conducive work environment and a fair compensation system play a significant role in improving employee performance. A good work environment includes both physical and non-physical aspects, while compensation encompasses salary, benefits, and other rewards. PT GOS Indoraya has made several efforts to improve employee performance, but there is still potential for further development. This study provides recommendations for the company to conduct regular evaluations of the work environment and compensation system, as well as develop more comprehensive training and career development programs.